Unsur-Unsur Surealisme dalam Puisi “Syaiun Sayabqa Bainana” Karya Faruq Juwaidah - Kamil, Moh (Universitas Muhammadiyah Gorontalo, 2023)
This study aims to describe the elements of surrealism found in the poem